2001
DOI: 10.1097/00005344-200112000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone Improves Left Ventricular Diastolic Function and Decreases Collagen Accumulation in Prediabetic Stage of a Type II Diabetic Rat

Abstract: This study investigated the effect of pioglitazone, an insulin sensitizer, on metabolic abnormalities and oxidative stress as a cause of myocardial collagen accumulation in prediabetic rat hearts. Twenty male diabetic rats and 9 male nondiabetic age-matched rats were used. The diabetic rats were divided into two groups: diabetic treated and untreated. Pioglitazone was mixed in rat chow fed to the diabetic treated group (0.01%). Treatment duration was 5 weeks. At baseline (15 weeks) and 20 weeks of age, blood g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
1
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 22 publications
2
52
1
3
Order By: Relevance
“…An insulin sensitiser (troglitazone) has been shown to protect against relaxation abnormalities caused by hyperglycaemia [27] and pioglitazone decreased LV collagen accumulation and improved LV diastolic function of prediabetic rat hearts [28]. Similarly, regular insulin treatment in type I diabetics is associated with normal or nearly normal diastolic function in young patients with diabetes of short duration [29] or less severe diastolic dysfunction in type 1 diabetic patients with a relatively higher HbA 1 c value or longer duration of the known disease compared with type 2 diabetic patients [30].…”
Section: Discussionmentioning
confidence: 99%
“…An insulin sensitiser (troglitazone) has been shown to protect against relaxation abnormalities caused by hyperglycaemia [27] and pioglitazone decreased LV collagen accumulation and improved LV diastolic function of prediabetic rat hearts [28]. Similarly, regular insulin treatment in type I diabetics is associated with normal or nearly normal diastolic function in young patients with diabetes of short duration [29] or less severe diastolic dysfunction in type 1 diabetic patients with a relatively higher HbA 1 c value or longer duration of the known disease compared with type 2 diabetic patients [30].…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20] In animals, thiazolidinediones have been shown to improve cardiac contractile function directly or indirectly by enhancing insulin sensitivity and reducing inflammation and oxidative stress. [1][2][3]19 The action of thiazolidinediones on diastolic myocardial function in relation to these factors has not yet been demonstrated in man, however.Given the high occurrence of diastolic myocardial dysfunction in patients with T2DM and its prognostic relevance, [20][21][22] we tested the hypothesis that the thiazolidinedione rosiglitazone, versus the sulfonylurea glimepiride, may improve diastolic myocardial function in these patients by simultaneously reducing oxidative stress and/or inflammation. Accordingly, the primary objective was to evaluate the change of diastolic myocardial function, measured as early diastolic myocardial velocity by pulsed tissue Doppler, after 16 weeks of oral treatment with rosiglitazone compared with glimepiride in patients with type 2 diabetes but without overt heart disease.…”
mentioning
confidence: 99%
“…In animal models, PPARγ agonists improve contractility and systolic performance, [78][79][80][81] enhance diastolic performance, [79][80][81][82] and decrease cardiac hypertrophy independent of loading conditions. [83][84][85] Similarly, randomised controlled trials of patients with DM have demonstrated no untoward effects on cardiac performance, assessed using echocardiography, and some trends toward improved function associated with longer-term TZD therapy. 78,86 The mechanism contributing to peripheral oedema and incremental risk for CHF is most likely to be alteration of sodium handling resulting in net volume retention.…”
Section: Cardiovascular Clinical Outcomes Trialsmentioning
confidence: 98%